PROMOTING PROBLEM-BASED LEARNING IN ADULT ENGLISH LANGUAGE TEACHING: WHAT, HOW, AND WHY - Buyun Khulel; Armin Fani (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2017)
This present paper was aimed to promote problem-based learning in adult English language teaching. The change of curriculum that used scientific approach was asked the teachers to use the suitable method in teaching learning process. One of the methods can be used by teachers is problem-based learning. Problem-based learning took the problem as the core of the process. The teaching learning process shifted to be more students centered and the teachers just facilitated them. By applying problem-based learning, the teachers provided some skills needed by the students to face the 21st century competition. According to Pacific Policy Research Centre (2010), those skills are communication and collaboration, critical thinking and problem solving, and creativity and innovation